The contribution of the International Criminal Tribunal for Rwanda to the development and enforcement of international humanitarian law in Africa - Benneh, Emmanueal Yaw (University of Pretoria, 2006)
Supervised by Mr. Emmanuel Yaw Benneh at the Faculty of Law, University of Ghana